WRITING THERAPY SEBAGAI HEALING MIND SET BAGI MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING - Amri, Khairul; Darwis, Muhammad; Saputri, Nor Mita Ika; Daulay, Ismail Rahmad (Jurnal Pengabdian Mitra Masyarakat, 2024)
The problems that will be resolved in this PKM consist of: (a) some students have experienced things that were painful and caused trauma, but have not been able to recover (b) students have an underestimation of themselves, and (c) students need assistance to healing mindset in dealing with life. The targets for this PKM were 20 students of the BK FKIP UM-Tapsel study program in the form of group counseling. The solution offered is training in writing about traumatic experiences for students for two months, after which group counseling will be carried out for students for two months. For four months, these meetings have included training in writing about past experiences, expressing writing along with a healing mindset in the form of public speaking, listening to other students' life experiences, and empathizing with other students' experiences.